Composition of positions for car-repair flexible flow and method of car transportation among them by means of transporter - Myamlin, V. V.; Myamlin, S. V.; Azimov, R. R.; Mihalchuk, A. M. (Science and Transport Progress, 2012)
Main causes affecting adversely functioning the traditional car-repair flow lines are defined. The composition of car-repair section using non-synchronous and flexible flow of cars repair is proposed. Design features of different transport vehicles for moving the rolling stock among parallel tracks are analyzed. A method for moving the units among the positions of flexible car-repair flow is described. The operational principle and design features of proposed transporter are demonstrated.